Education For Women in The Global Era of Islamic Perspectives - Mahbub Junaidi; Mahmutarom Mahmutarom; Ifada Retno Ekaningrum; Khotimah Suryani (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
Some civilizations consider women second-class human beings compared to men; others view women and men as equal and equal. The first creates a negative stigma for women who are socially active, resulting in restrictions on access to education. The second view gives rise to an excessive attitude that women must be the same as men. This research aims to explore, study, and discuss Islamic views on the position of women. The Islamic view in question was based on the texts of the Al-Qur’an and hadith, in which classical and contemporary Muslim intellectuals gave adequate explanations or interpretations. This study was a type of library research where the researcher used a descriptive-analytical method by adopting Maudlu’i interpretation in the study of the Al-Qur’an and hadith with a hermeneutical approach. The researcher's procedure was to start the study with a historical study of women’s education in various world cultures and civilizations, continue with women’s Islamic perspective, and continue with studies on the position of women in Islam and women’s education from an Islamic perspective. An in-depth analysis of women's education's global relevance and implications was conducted. This research concluded that Islam views women as having the same dignity and worth as men. Many verses of the Al-Qur’an and hadiths of the Prophet Muhammad SAW explain the position of women and that there was no discrimination in them, as well as in matters of education. No verses in the Al-Qur’an or Hadith of the Prophet Muhammad SAW specifically specified education for men only and excluded women.